Varicella vaccination in Europe – taking the practical approach - Sadzot-Delvaux Catherine (BMC Medicine, 2009)
Abstract Varicella is a common viral disease affecting almost the entire birth cohort. Although usually self-limiting, some cases of varicella can be serious, with 2 to 6% of cases attending a general practice resulting in complications. The hospitalisation rate for varicella in Europe ranges from 1.3 to 4.5 per 100,000 population/year and up to 10.1% of hospitalised patients report permanent or possible permanent sequelae (for example, scarring or ataxia). However, in many countries the epidemiology of varicella remains largely unknown or incomplete. In countries where routine childhood vaccination against varicella has been implemented, it has had a positive effect on disease prevention and control. Furthermore, mathematical models indicate that this intervention strategy may provide economic benefits for the individual and society. Despite this evidence and recommendations for varicella vaccination by official bodies such as the World Health Organization, and scientific experts in the field, the majority of European countries (with the exception of Germany and Greece) have delayed decisions on implementation of routine childhood varicella vaccination, choosing instead to vaccinate high-risk groups or not to vaccinate at all. In this paper, members of the Working Against Varicella in Europe group consider the practicalities of introducing routine childhood varicella vaccination in Europe, discussing the benefits and challenges of different vaccination options (vaccination vs. no vaccination, routine vaccination of infants vs. vaccination of susceptible adolescents or adults, two doses vs. one dose of varicella vaccine, monovalent varicella vaccines vs. tetravalent measles, mumps, rubella and varicella vaccines, as well as the optimal interval between two doses of measles, mumps, rubella and varicella vaccines). Assessment of the epidemiology of varicella in Europe and evidence for the effectiveness of varicella vaccination provides support for routine childhood programmes in Europe. Although European countries are faced with challenges or uncertainties that may have delayed implementation of a childhood vaccination programme, many of these concerns remain hypothetical and with new opportunities offered by combined measles, mumps, rubella and varicella vaccines, reassessment may be timely.